THE PRAGMATIC ADEQUACY IN CONVEYING THE CONCEPT HAPPINESS FROM ENGLISH INTO UZBEK - Ozoda Mustafaqulova (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
This scientific article discusses the pragmatic adequacy of translating the concept of happiness from English to Uzbek.